THE The Role of EM4 (Effective Microorganisms) in Solid Waste-Powered Microbial Fuel Cells: Investigating Voltage Output and Electrical Conductivity For Bioelectricity Generation - Ida MUNFARIDA; Shinfi Wazna AUVARIA (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
The increasing global demand for renewable energy and sustainable waste management solutions has inspired interest in microbial fuel cells (MFCs) as a dual-purpose technology for bioelectricity generation and waste treatment. This study explores the role of EM4, a consortium of effective microorganisms, in enhancing the voltage output and electrical conductivity of solid waste-powered MFCs. A batch system bioreactor assessed the impact of varying organic waste-to-zeolite ratios on MFC performance. The results demonstrated that a 1:1 ratio of organic waste to zeolite produced the highest electrical conductivity (3160 µS/cm) and the most substantial voltage output (777.5 mV) by day three of the experiment. Statistical analysis, including ANOVA and Kruskal-Wallis tests, revealed significant differences in voltage output across treatments, with a positive correlation between electrical conductivity and voltage production. These findings highlight the potential of integrating EM4 and conductive materials like zeolite to optimize bioelectricity generation in MFCs, contributing to the advancement of sustainable energy technologies.